Canagliflozin Suppresses Atrial Remodeling in a Canine Atrial Fibrillation Model - Nishinarita, Ryo; Niwano, Shinichi; Niwano, Hiroe; Nakamura, Hironori; Saito, Daiki; Sato, Tetsuro; Matsuura, Gen; Arakawa, Yuki; Kobayashi, Shuhei; Shirakawa, Yuki; Horiguchi, Ai; Ishizue, Naruya; et al. (Journal of the American Heart Association, 2021)
Background Recent clinical trials have demonstrated the possible pleiotropic effects of SGLT2 (sodium-glucose cotransporter 2) inhibitors in clinical cardiovascular diseases. Atrial electrical and structural remodeling is important as an atrial fibrillation (AF) substrate. Methods and Results The present study assessed the effect of canagliflozin (CAN), an SGLT2 inhibitor, on atrial remodeling in a canine AF model. The study included 12 beagle dogs, with 10 receiving continuous rapid atrial pacing and 2 acting as the nonpacing group. The 10 dogs that received continuous rapid atrial pacing for 3 weeks were subdivided as follows: pacing control group (n=5) and pacing+CAN (3 mg/kg per day) group (n=5). The atrial effective refractory period, conduction velocity, and AF inducibility were evaluated weekly through atrial epicardial wires. After the protocol, atrial tissues were sampled for histological examination. The degree of reactive oxygen species expression was evaluated by dihydroethidium staining. The atrial effective refractory period reduction was smaller ( =0.06) and the degree of conduction velocity decrease was smaller in the pacing+CAN group compared with the pacing control group ( =0.009). The AF inducibility gradually increased in the pacing control group, but such an increase was suppressed in the pacing+CAN group ( =0.011). The pacing control group exhibited interstitial fibrosis and enhanced oxidative stress, which were suppressed in the pacing+CAN group. Conclusions CAN and possibly other SGLT2 inhibitors might be useful for preventing AF and suppressing the promotion of atrial remodeling as an AF substrate.